The The Relationship between Premarital Free Sex knowledge and Attitude in Preventing Free Sex in Teenagers of SMA N 1 Sragi: Hubungan Pengetahuan Mengenai Seks Bebas Pranikah Dengan Sikap Dalam Mencegah Seks Bebas Pada Remaja Di SMA N 1 Sragi - Devita Rachmawati; Emi Nurlaela (PENA NURSING, 2025)
ABSTRACT Devita Rachmawati1, Emi Nurlaela2 The Relationship between Premarital Free Sex knowledge and Attitude in Preventing Free Sex in Teenagers of SMA N 1 Sragi Background: Premarital sex cases are common among teenagers. This condition is against the norms of society, morality, and religion. This study aims to determine the relationship between knowledge about premarital free sex and attitudes in preventing free sex in adolescents. Methods: Correlational design quantitative research with a cross-sectional approach. The location of the research was SMA Negeri 1 Sragi. The sample was taken by cluster random sampling as many as 62 respondents in classes X, XI, and XII. The research instrument is a knowledge and attitude questionnaire that has been tested for validity and reliability. The results of the validity test of the knowledge questionnaire with a Cronbach's alpha value of 0.790 and an attitude with a Cronbach's alpha value of 0.873. Results: The results showed that the knowledge was unfavourable as many as 50 respondents (80.6%) and the attitude of adolescents was unfavourable as many as 31 respondents (50%). The Chi Square test shows a p value of 0.748> α (0.05), meaning that there is no relationship between knowledge about premarital free sex and attitudes in preventing free sex in adolescents. Conclusion: There is no correlation between the knowledge of premarital free sex and attitudes in preventing free sex on adolescents at SMA N 1 Sragi. It is being suggest that schools are encouraged to conduct socialization about reproductive health and the impact of premarital free sex during the learning process to prevent cases of premarital promiscuous sex in adolescents from increasing. Keywords: Knowledge, Attitude, Free Sex References: 63 (2015-2024)